The features of lipid spectrum components in hypertensive patients - Buriak, V. V.; Mykytenko, Ya. V.; Буряк, Віктор Валерійович (Запорізький державний медико-фармацевтичний університет, 2024)
Aim: to analyze the lipid spectrum components in hypertensive patients.
Keywords: тези доповідей